2020
DOI: 10.21203/rs.2.24075/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Relationship between Household Chaos and Child, Parent, and Family Outcomes: A Systematic Scoping Review

Abstract: Background: Household chaos, represented by the level of disorganisation or environmental confusion in the home, has been associated with a range of adverse child and family outcomes. This review aims to (1) identify how household chaos is measured, (2) chart study details of household chaos literature, and (3) map the existing literature with respect to the relationship between household chaos and child, parent, and family outcomes. We expect that this review will highlight the need to consider the importance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 91 publications
(178 reference statements)
1
20
0
Order By: Relevance
“…According to existing evidence in adolescence, lower family income could predict worse psychological and academic status (Davis-Kean, 2005;Shapero & Steinberg, 2013), and the limited living space could predict poor mental health and low quality of life (Ravens-Sieberer et al, 2021). Moreover, a review on family chaos concluded its negative effects on adolescent academic development, socioemotional well-being, and mental and physical health (Marsh et al, 2020). Jointly, the present study considered family economic status, per capita living space, and home chaos as indicators of the whole family climate and discovered their influences on adolescent life changes.…”
Section: Family Interactionsmentioning
confidence: 99%
“…According to existing evidence in adolescence, lower family income could predict worse psychological and academic status (Davis-Kean, 2005;Shapero & Steinberg, 2013), and the limited living space could predict poor mental health and low quality of life (Ravens-Sieberer et al, 2021). Moreover, a review on family chaos concluded its negative effects on adolescent academic development, socioemotional well-being, and mental and physical health (Marsh et al, 2020). Jointly, the present study considered family economic status, per capita living space, and home chaos as indicators of the whole family climate and discovered their influences on adolescent life changes.…”
Section: Family Interactionsmentioning
confidence: 99%
“…Second, in the long term, periodic early-life environments may facilitate anticipations and predictions, leading to better top-down modulated entrainment, manifesting behaviourally as better executive control. There is ample evidence that temporal regularities are important during development -for example, child-directed speech is more periodic ( 97,98 (see also [99][100][101] )), and that aperiodic environments may associate with worse EF outcomes [102][103][104][105] . However, direct associations between periodicities in the early-life environment and short-and long-term facilitatory effects on neural processing of environmental information remain untested.…”
Section: Temporal Regularitiesmentioning
confidence: 99%
“…Note, household chaos refers to the level of disorganisation, noise, and environmental confusion in the home, and has been associated with a range of adverse child outcomes. It has been suggested that household chaos impacts children by increasing levels of stress and distraction, interfering with children's attention allocation and information processing skills, and compromising positive parent-child interactions and parental responsiveness [53].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…• Household chaos, which represents the level of disorganisation, environmental confusion, and background noise and distractions in the home [53], was assessed using the 15-item Chaos, Hubbub, and Order Scale (CHAOS) [58], and engagement in routines of daily life using the Daily Living Routines subscale of the Child Routine Inventory (CRI) [59].…”
Section: Outcome Measuresmentioning
confidence: 99%